ANALYSIS OPTIMALIZATION OF BPHTB TAX POLICY TO BOOST LOCAL REVENUE - Farman, Fanji; Erpi Rahman; Fahrul Alam Masruri; Maman Nurochman (ITB AAS Indonesia Surakarta, 2025)
This study examines the challenges in managing the Land and Building Rights Acquisition Fee (BPHTB) tax in Sumedang Regency, with a focus on improving the accuracy of target setting and enhancing administrative efficiency. The research aims to evaluate the BPHTB target-setting system and revenue realization, providing policy recommendations to improve effectiveness and transparency. Using a qualitative descriptive approach, data were gathered through literature reviews, interviews with key stakeholders such as the BPD and PPAT, and observations of current practices. The results indicate that BPHTB targets often fail to align with actual economic conditions due to inaccurate data and the limited application of relevant indicators, which hinders optimal revenue generation. The study suggests revising BPHTB rates and Non-Tax Object Selling Price thresholds based on economic growth benchmarks, adopting a data-driven planning system, and strengthening coordination among BPN, PPAT, and BPD. Proposed incentives and enhanced capacity for tax administration are expected to increase taxpayer compliance and optimize revenue collection. This research highlights the importance of improving target-setting processes and tax administration to enhance fiscal sustainability in Sumedang Regency.